2017
DOI: 10.1038/s41598-017-07949-4
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal transepithelial permeability of oxytocin into the blood is dependent on the receptor for advanced glycation end products in mice

Abstract: Plasma oxytocin (OT) originates from secretion from the pituitary gland into the circulation and from absorption of OT in mother’s milk into the blood via intestinal permeability. However, the molecular mechanism underlying the absorption of OT remains unclear. Here, we report that plasma OT concentrations increased within 10 min after oral delivery in postnatal day 1–7 mice. However, in Receptors for Advanced Glycation End Products (RAGE) knockout mice after postnatal day 3, an identical OT increase was not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 69 publications
1
45
0
Order By: Relevance
“…RAGE-mediated oxytocin transport from the intestinal tract into the blood circulation across the intestinal barrier was also found to occur in mice 29 . This RAGE-dependent intestinal permeability was demonstrated following the oral administration of oxytocin in mouse pups at the very narrow window of postnatal days 4-6, during which the barrier will be formed but still digestion is not active.…”
Section: Possible Routes and Functions Of Oxytocinmentioning
confidence: 89%
See 1 more Smart Citation
“…RAGE-mediated oxytocin transport from the intestinal tract into the blood circulation across the intestinal barrier was also found to occur in mice 29 . This RAGE-dependent intestinal permeability was demonstrated following the oral administration of oxytocin in mouse pups at the very narrow window of postnatal days 4-6, during which the barrier will be formed but still digestion is not active.…”
Section: Possible Routes and Functions Of Oxytocinmentioning
confidence: 89%
“…This RAGE-dependent intestinal permeability was demonstrated following the oral administration of oxytocin in mouse pups at the very narrow window of postnatal days 4-6, during which the barrier will be formed but still digestion is not active. The blood oxytocin levels of the mice were high at approximately 1-3 days after birth, likely due to nonspecific bulk absorption, and no uptake of oxytocin was observed after 7 days when the same concentration of oxytocin was orally applied 29 . Although it was previously reported that oxytocin is absorbed in neonates and infants, our results show that oxytocin transport across the intestinal barrier is RAGE-dependent 29 .…”
Section: Possible Routes and Functions Of Oxytocinmentioning
confidence: 95%
“…Recently, Higashida et al [145] reported that oxytocin is transmitted into blood in the intestinal tract via the mediation of receptors for glycation end products in adult mice. Oral oxytocin supplementation could be another potential anti-obesity treatment.…”
Section: Resultsmentioning
confidence: 99%
“…CD38 and/or CD157 can be referred to as a neuro-entero-immunological regulator [6,18]. Interestingly, even for CD38, it is reported that the specific SNP (rs3796863) of CD38 was originally documented as an association with ASD [21], with close relation to gastrointestinal dysfunction, one of the typical symptoms of ASD [95].…”
Section: Conclusion and Perspectivementioning
confidence: 99%